2015
DOI: 10.1017/s0033291715000525
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related anhedonia is associated with ventral striatum reactivity to reward and transdiagnostic psychiatric symptomatology

Abstract: Background Early life stress (ELS) is consistently associated with increased risk for subsequent psychopathology. Individual differences in neural response to reward may confer vulnerability to stress-related psychopathology. Using data from the ongoing Duke Neurogenetics Study, the present study examined whether reward-related ventral striatum (VS) reactivity moderates the relationship between retrospectively reported ELS and anhedonic symptomatology. We further assessed whether individual differences in rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 87 publications
6
85
0
1
Order By: Relevance
“…This may be partially explained by likely inherent differences between accumbal responsiveness to drugs of abuse as employed in animal studies, and to the anticipation of monetary-based reward as is typically utilized in human experiments. However, it should be noted that the studies showing blunted accumbal responses to reward following chronic juvenile stress also found that NAc hypoactivity strongly predicted symptoms of anhedonia and depression (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015). Moreover, anhedonia in participants exposed to repeated juvenile stress was linked to problematic alcohol use arising from the use of substances as a coping mechanism (Corral-Frias et al, 2015).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be partially explained by likely inherent differences between accumbal responsiveness to drugs of abuse as employed in animal studies, and to the anticipation of monetary-based reward as is typically utilized in human experiments. However, it should be noted that the studies showing blunted accumbal responses to reward following chronic juvenile stress also found that NAc hypoactivity strongly predicted symptoms of anhedonia and depression (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015). Moreover, anhedonia in participants exposed to repeated juvenile stress was linked to problematic alcohol use arising from the use of substances as a coping mechanism (Corral-Frias et al, 2015).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
“…However, it should be noted that the studies showing blunted accumbal responses to reward following chronic juvenile stress also found that NAc hypoactivity strongly predicted symptoms of anhedonia and depression (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015). Moreover, anhedonia in participants exposed to repeated juvenile stress was linked to problematic alcohol use arising from the use of substances as a coping mechanism (Corral-Frias et al, 2015). Interestingly, hyperactivity of the NAc in response to amphetamine has been reported in individuals who experienced juvenile stress, with the strength of activation being positively correlated with the degree of stress exposure (Oswald et al, 2014).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Child trauma is associated with anhedonia less strongly in young adults with high ventral striatum reactivity to reward [43]. Lower levels of anhedonia, in turn, are associated with reduced depression symptoms and problematic drinking following child trauma [43].…”
Section: Protective Factorsmentioning
confidence: 99%
“…Structural and functional changes are documented in the dopaminergic reward centers in the brain of animals subjected to early stress (Hall et al, 1999, Chocyk et al, 2015). Further, reduced response to reward in the ventral striatum, a key brain reward center, is documented in early-institutionalized youth (Goff et al, 2013) and adults reporting histories of early stress (Corral-Frías et al, 2015). We and others have found that trauma-related changes in brain function and connectivity correspond with diminished experience of positive affect rather than heightened negative affect (Nikolova et al, 2012, Marusak et al, 2015b), suggesting that robust brain reward function and associated levels of positive affect may be protective against stress-related psychopathology.…”
Section: Trauma Associated Disruption In Neural Volume Structure Andmentioning
confidence: 99%